2020
DOI: 10.3390/agronomy10020209
|View full text |Cite
|
Sign up to set email alerts
|

Higher Radiation Use Efficiency Produces Greater Biomass Before Heading and Grain Yield in Super Hybrid Rice

Abstract: To reveal the physiological mechanism underlying the yield advantage of super hybrid rice compared with inbred super rice, a super hybrid rice cultivar Yliangyou 3218 (YLY) and an inbred super rice cultivar Zhendao 11 (ZD) were field grown under five nitrogen (N) fertilizer rates in 2016 and 2017. The average grain yield of YLY across nitrogen fertilizer rates was 10.1 t ha−1 in 2016 and 9.7 t ha−1 in 2017, 29.6% and 21.3% higher than that of ZD in 2016 and 2017, respectively. YLY showed higher above-ground bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, the LAI was the highest in the LDHF treatment during the early stage of rice development, indicating that the fertilizer application had a greater effect on the LAI than the transplanting density during this period. Pan et al (2020) indicated that the aboveground biomass at the tassel stage determines the yield [35], with about 60-80% of the yield coming from photosynthetic products after tasseling [36]. Katsura et al (2008) found that high rice yields were mainly attributed to high dry matter accumulation [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the LAI was the highest in the LDHF treatment during the early stage of rice development, indicating that the fertilizer application had a greater effect on the LAI than the transplanting density during this period. Pan et al (2020) indicated that the aboveground biomass at the tassel stage determines the yield [35], with about 60-80% of the yield coming from photosynthetic products after tasseling [36]. Katsura et al (2008) found that high rice yields were mainly attributed to high dry matter accumulation [29].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, to break the yield ceiling of rice production, it was essential to establish the mechanism underlying the yield advantage and photosynthetic capacity in super hybrid rice and inbred super rice. Our previous study found that Yliangyou 3218 (YLY 3218) achieved a high yield due to its improved radiation use efficiency ( Pan et al., 2020 ). Therefore, a comparison in the yield performance and leaf-level photosynthesis was performed between two super hybrid rice Y-liangyou 3218 (YLY3218) and Y-liangyou 5867 (YLY5867), and two inbred super rice Zhendao11 (ZD11) and Nanjing9108 (NJ9108) at two growth stages (tiller stage and flowering stage) in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…To break the yield barriers, China initiated a “super rice” megaproject in 1996, which resulted in the release of more than 131 “super rice” varieties with grain yields of more than 12 t ha −1 [ 14 , 15 ]. The increase in yield was attributed to an increase in sink size, higher source capacity, and higher dry-matter production [ 16 ].…”
Section: Introductionmentioning
confidence: 99%